Cover Feature: First Total Synthesis of Phytoprostanes with Prostaglandin‐Like Configuration, Evidence for Their Formation in Edible Vegetable Oils and Orienting Study of Their Biological Activity (Chem. Eur. J. 37/2021). Issue 37 (9th June 2021) - Smrček, Jakub; Hájek, Miroslav; Hodek, Ondřej; Čížek, Karel; Pohl, Radek; Jahn, Emanuela; Galano, Jean‐Marie; Oger, Camille; Durand, Thierry; Cvačka, Josef; Jahn, Ullrich
Abstract : Phytoglandins from the reaction flask enable their identification in Nature. Hypothetical plant‐based prostaglandin analogs were obtained by a 15‐step asymmetric total synthesis. They were applied as an analytical standard in a detailed LC‐MS/MS study confirming phytoglandin formation in autoxidized linolenic acid and in various edible vegetable oils in sizeable quantities. More information can be found in the Full Paper by U. Jahn et al. (DOI: 10.1002/chem.202100872 ).